Biomaterial‐Induction of a Transplantable Angiosome. (4th November 2019) - Charbonnier, Baptiste; Maillard, Sophie; Sayed, Omaer; Baradaran, Aslan; Mangat, Harshdeep; Dalisson, Benjamin; Zhang, Zishuai; Zhang, Yu‐Ling; Hussain, Sabah N. A.; Mayaki, Dominique; Seitz, Hermann; Harvey, Edward J.; et al.
Abstract: Creating transplantable vascular networks (angiosomes) that are fed and drained by vessels large enough to be surgically reconnected is key to harnessing the potential of regenerative medicine and advancing reconstructive surgical techniques. Currently, the only way to create a new angiosome is nontrivial and involves pressurizing a vein graft by its surgical attachment to an artery forming an arteriovenous loop (AVL). Material induction of a venous angiosome is reported, by placement of a 3D printed microporous monetite scaffold around a vein and its transplantability is further demonstrated. When the transplanted venosome is cut, it bleeds, illustrating potential reconstructive functionality. The volume of blood vessels generated by biomaterial‐induction is as great as by AVL. Direct contact of the material with the vein does not appear to be critical to luminal sprouting, and wrapping the implant in a silicone membrane significantly reduces sprouting. Pilot studies with microporous polymeric scaffolds induce far less vascular invasion. After 4 weeks, monetite scaffolds are extensively vascularized and can be transplanted to an arterial vessel. This report is significant since a lack of tools to control vascular generation is an impediment to the treatment of several conditions that give rise to tissue ischemia and tissue reconstruction. Abstract : Luminal branching is unexpectedly induced simply by placing a vein within microporous calcium phosphate. Only osteoinductive biomaterials have been reported previously, and this is thought to be the first report of an angio‐inductive material. The data point to a possible bioinorganic effect, wherein the degradation of the material both releases a stimulatory ionic milieu and creates space for the developing angiosome.